A method for planning human robot shared tasks. (August 2018) - Michalos, George; Spiliotopoulos, Jason; Makris, Sotiris; Chryssolouris, George
Highlights: Implementation of a multi criteria method for the planning of shared human robot assembly tasks. An intelligent algorithm automatically generates and examines alternative scenarios. The algorithm performs the joint planning of task-to-resource assignments and cell layout design. Ergonomics, quality, technical feasibility and productivity criteria are used for the evaluation. The system has been validated in a case study from the automotive industry. Abstract: A multi criteria method, in support of the planning of shared human robot assembly tasks is presented in this paper. CAD models are used for the extraction of a product's assembly sequence, whilst an algorithm is applied for the generation and examination of alternative assignment scenarios. The design algorithm performs the joint planning of task-to-resource assignment and cell layout at the same time. The evaluation of each planning scenario against a set of ergonomics, quality and productivity criteria is made for the identification of the most efficient ones. The method's implementation, in the form of a prototype planning tool (Task Planner), enables its application to a pilot case from the automotive industry. The results indicate that the method can provide high quality solutions with respect to the end users' criteria and has potential applicability as a decision making support tool in the planning stage.